Tele-operated robotic ultrasound system for medical diagnosis. (September 2021) - Duan, Bin; Xiong, Linfei; Guan, Xiaolong; Fu, Yongqing; Zhang, Yongwei
Highlights: The operation method of our robot control console is in line with doctor's habits. The robot control strategy meets the requirements of clinical use. The system could be used with different network conditions. The system verified the clinical effectiveness of the remote ultrasound system. Abstract: Ultrasound scanning is a commonly used diagnostic method because of its high efficiency and limited side effects. However, unlike computed tomography (CT) and magnetic resonance imaging (MRI), ultrasound scanning requires professional doctors. In China, experienced ultrasound doctors are concentrated in big hospitals. Ultrasound treatment cannot be performed effectively in most rural areas. To provide equal ultrasound treatments to those areas, a novel remote robotic ultrasound scanning system is introduced in this work. The system can be divided into two parts: doctor-side and patient-side. Using our system, doctors could control the robotic arm and ultrasound machine remotely. Integrated position and force control are applied in our system to recur the hand movements of the doctor as well as maintaining flexible contact with the patient body. Real-time audio and video transmission is also realized in our system. The system can be used with the wired network, 4G, and 5G wireless network. The system was tested on 95 subjects in clinical trials. The results show that the remote ultrasound scanning task can be accomplished using our system. The ultrasound images obtained by our system have a high medical diagnostic value.